Contorted polycyclic aromatic hydrocarbons with cove regions and zig-zag edges. Issue 60 (13th July 2017) - Chen, Yulan; Marszalek, Tomasz; Fritz, Torsten; Baumgarten, Martin; Wagner, Manfred; Pisula, Wojciech; Chen, Long; Müllen, Klaus
Abstract : Three tetrapyrene-fused benzocoronenes were synthesized by a "bottom-up" approach, which offers a facile access to extended polycyclic aromatic hydrocarbons with cove regions and zig-zag edges. Abstract : A series of tetrapyrene-fused benzocoronenes was synthesized by a "bottom-up" approach, which offers a facile access to extended polycyclic aromatic hydrocarbons with concave π-surfaces, cove regions and zig-zag edges.